Reševanje nekaterih skladenjskih vprašanj v slovenščini glede na razpoložljive teorije in metode - Žele, Andreja (Slavistična revija, 2008)
The paper points out and treats in more detail some syntactic pecularities that are the result of the inequality or, rather incongruence of logical-semantic and expressive levels within the same clausal sentence and/or a particular textual unit of Slovene. From the standpoint of the incongruence between a given semantic proposition and the required (expressive) clause-formation, the author treats the obligatory expressible non-propositional, i.e., non-participant, components on the one hand, and the propositional, i.e., participant, components with more than one syntactic-functional and expressive equivalent on the other.
Keywords: skladnja; slovenščina